Parvoviruses NS1 oncolytic attributes: mechanistic insights and synergistic anti-tumor therapeutic strategies - Haseeb, Abdul; Yousaf, Wafa; Cao, Zhigang; Fan, Kuohai; Sun, Na; Sun, Panpan; Sun, Yaogui; Yang, Huizhen; Yin, Wei; Zhang, Hua; Zhang, Zhenbiao; Zhong, Jia; et al. (Frontiers in Microbiology, 2025)
Parvovirus is comprised of a single-stranded DNA structure, encompassing distinct structural and non-structural proteins. Structural proteins are referred as viral proteins, which facilitate for the viral capsid. Among non-structural proteins, NS1 is the most significant, exhibiting substantial characteristics related to viral replication, pathogenicity, and is notably recognized for its remarkable oncolytic properties. NS1 possesses a distinctive structure; however, it differs across different parvovirus species. It is comprised of three fundamental domains: the N-terminal origin binding, helicase domain, and C-terminal domain, all crucial for significant functions. In several parvovirus species, such as CPV, MVM, BPV, and HPV-B19, NS1 halts the cell cycle at distinct stages, including G1, G2, and S phases of the life cycle, and induces cell death. Predominantly, parvovirus NS1 has also been significantly recognized to induce tumor cell death in vitro and in vivo by following different mechanisms, including cytotoxicity, autophagy, immunomodulation, mitochondrial depolarization, and most significantly, apoptosis. This may lead to several intracellular changes, including reactive oxygen species (ROS) level, mitochondria, PARP, caspase, and their subtype activation, ultimately leading to DNA and other cellular level changes, which facilitate apoptotic cell death. These characteristics of NS1 and its combinational therapy revealed a wide range of evidential research that demonstrated its anti-tumor effects through several pathways and can even induce a substantial activation of the immune response. This review mainly aims to elucidate the oncolytic attributes of parvoviral NS1, focusing on its capabilities and the mechanism demonstrated in prior research. It also addresses genetic engineering and combinational therapy aimed at augmenting the oncolytic efficacy of NS1 for more potent application as a tumor therapeutic agent. The increasing focus on virotherapy and precision oncology underscores the necessity for thorough exploration of the molecular mechanisms, delivery techniques, and clinical implications of NS1, thereby facilitating the development of innovative, tumor-selective anticancer approaches.